Enfoque e interpretación de las manifestaciones del síndrome depresivo desde la medicina tradicional china (2012)
Depression is currently recognized as one of the main public health problems. This disorder has a strong impact on quality of life and generates high costs to the healthcare system. Despite the available treatments, there is a high rate of recurrence and treatment abandonment, increasing the importance of Traditional Chinese Medicine (TCM), which goes back more than 2000 years. At present, both TCM and Western medicine form part of the state-provided health services in China. The theory behind TCM describes health as a balance in the body's energy. Disease is explained by theories of Yin-Yang, the five elements, Zang-Fu, and channels-collaterals. Currently, some studies - both in the East and West - have confirmed the veracity of ancient texts on the potential of acupuncture in the diagnosis and treatment of depression. The focus of this therapeutic modality improves patient adherence to treatment and consequently reduces the possibility of future recurrences. For TCM, although the other organs and viscera are also involved, the organs mainly affected in cases of depression are the Liver and Heart. The aim of this review is to provide a clear and concise approach, from the perspective of TCM, to the management of depression, without ignoring the importance of the perspective of allopathic medicine.